Delaware public records - Delaware
Lists of taxable persons and estates assessed, 1776; sketch of Delaware state seal of 1776; report by the committee of council of Delaware regarding the militia, 1777; oath of allegiance to the state of Delaware, 1778; list of county officials, 1792; and petitions concerning the Circuit Court schedule, circa 1797.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Oath of allegiance and report of the committee of council of Delaware formerly cataloged under George Craghead, one of the signers of the documents.
Keywords: Craghead, George; Delaware. -- Militia; Delaware -- Officials and employees; Allegiance -- Delaware; Circuit courts -- Delaware; County officials and employees -- Delaware; Oaths -- Delaware; Public records -- Delaware; Taxation -- Delaware; Delaware -- History; Delaware -- Militia; Delaware -- Politics and government -- 1775-1865.; Delaware -- Seal